Rapid and Sensitive Recombinase Polymerase Amplification Combined With Lateral Flow Strip for Detecting African Swine Fever Virus - Miao, Faming; Zhang, Jingyuan; Li, Nan; Chen, Teng; Wang, Lidong; Zhang, Fei; Mi, Lijuan; Zhang, Jinxia; Wang, Shuchao; Wang, Ying; Zhou, Xintao; Zhang, Yanyan; et al. (Frontiers in Microbiology, 2019)
African swine fever virus (ASFV), the etiological agent of African swine fever, a haemorrhagic fever of domestic pigs, has devastating consequences for the pig farming industry. More than 1,000,000 pigs have been slaughtered since 3 August 2018 in China. However, vaccines or drugs for ASF have yet to be developed. As such, a rapid test that can accurately detect ASFV on-site is important to the timely implementation of control measures. In this study, we developed a rapid test that combines recombinase polymerase amplification (RPA) of the ASFV p72 gene, with lateral flow detection (LFD). Results showed that the sensitivity of RPA-LFD for ASFV was 150 copies per reaction within 10 min at 38 °C. The assay was highly specific to ASFV and had no cross-reactions with other porcine viruses, including classical swine fever virus. A total of 145 field samples were examined using our method, and the agreement of the positive rate between RPA-LFD (10/145) and real-time PCR (10/145) was 100%. Overall, RPA-LFD provides a novel alternative for the simple, sensitive, and specific identification of ASFV and showed potential for on-site ASFV detection.